2016
DOI: 10.1093/jjco/hyv185
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Forkhead box protein k1 recruits TET1 to act as a tumor suppressor and is associated with MRI detection

Abstract: Objective: Today, more and more evidence suggests that Foxk proteins (Foxk1 and Foxk2) work as transcriptional repressors in different kinds of cancer, but whether Foxk1 has a role in mediating tumorigenesis in breast cancer, the evidence is rare. Methods: MCF-7 cells transfected with shFoxk1 displayed a mesenchymal morphology and reduced the expression of E-cadherin, and increased the expression of N-cadherin. Transwell invasion assay and living imaging assay show that the overexpression of Foxk1 could inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…We show here that a significant portion of mutant ASXL1's function is linked to FOXK1 and FOXK2, as more than 60% of genes differentially regulated by C-terminal truncation mutant ASXL1 are direct targets of FOXK1/K2. Although both transcriptional activation (Sukonina et al, 2019) and repression (Sun et al, 2016;Li et al, 2019) can be regulated by FOXK1 and FOXK2, our study supports the overlapping and transcriptional activation role of FOXK1/K2 and is consistent with the gene silencing role of H2AK119 mono-ubiquitination mediated by the PR-DUB complex. Supporting this notion, knockdown of FOXK1/K2 or deletion of mutant ASXL1 allele leads to decreased H2AK119 monoubiquitination at the promoter regions of FOXK1/K2 target genes (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…We show here that a significant portion of mutant ASXL1's function is linked to FOXK1 and FOXK2, as more than 60% of genes differentially regulated by C-terminal truncation mutant ASXL1 are direct targets of FOXK1/K2. Although both transcriptional activation (Sukonina et al, 2019) and repression (Sun et al, 2016;Li et al, 2019) can be regulated by FOXK1 and FOXK2, our study supports the overlapping and transcriptional activation role of FOXK1/K2 and is consistent with the gene silencing role of H2AK119 mono-ubiquitination mediated by the PR-DUB complex. Supporting this notion, knockdown of FOXK1/K2 or deletion of mutant ASXL1 allele leads to decreased H2AK119 monoubiquitination at the promoter regions of FOXK1/K2 target genes (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, the exact role of the FOXK1 and FOXK2 in cancer is still controversial. In breast cancer, Sun et al 20 reported that FOXK1 expression is lower in cancer tissue and cell lines; on the contrary, In contrast, Li et al 19 showed that the expression of FOXK1 was higher in cancer tissue. Moreover, high FOXK1 expression has been reported in the tumor tissue compared with normal tissue in several cancers, including gastric, hepatoma, ovarian, esophagus, and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression levels of the FOXK family members in cancers are still unclear. Sun et al 20 reported that FOXK1 expression is lower in breast cancer tissue and cell lines compared with normal tissue. In contrast, Li et al 19 showed that the expression of FOXK1 was higher in breast cancer tissue compared with adjacent-cancer tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro tube formation analysis was performed using growth factor-reduced Matrigel (BD Biosciences), as previously described. 16 Briefly, a 200 μL growth factor-reduced Matrigel was coated in the 24-well plates and then solidified at 37°C for 30 minutes. HUVECs were cultured with CM from MCF-7 cells that were transfected with vector, ISL1 or SCR, siISL1.…”
Section: Methodsmentioning
confidence: 99%